Association between serum cholesterol levels and nutritional status in school children aged 10-12 years - Fransiscus H Wulur; Recky Dj B Pieter (Indonesian Pediatric Society, 2003)
Background Hypercholesterolemia in children is an important riskfactor that causes coronary heart disease in the future. Nutritionalstatus, especially overweight/obesity, is associated with hyperc-holesterolemia.Objective To determine the prevalence of hypercholesterolemiaand its association with nutritional status.Methods This was a cross sectional study conducted during April-June 2001. Subjects consisted of children aged 10-12 year-oldregistered at primary schools in Manado, Tondano, and TandenganMinahasa. Data were analyzed using t test, z score, and chi-square.Results Of the 229 samples, 153 (66.8%) were boys and 76 (33.2%) were girls. The mean of total cholesterol level in boys was 179.46mg/dL (SD 33.44) and in girls was 180.95 mg/dL (SD 33.77) whichwas not significantly different (p>0.05). There were no differencesin either the number of children having â€œborderlineâ€ cholesterol level(170â€“199 mg/dL) or hypercholesterolemia (3200 mg/dL) betweenboth sexes. Of the 229 children, 65 (28.4%) had hypercholester-olemia. Of the 65 children, 37 (36%) came from the primary schoolin Manado, which was significant compared to the other schoollocations (p<0.05). Twenty-five (39%) children with hypercholes-terolemia had overweight nutritional status, which was significantcompared to the other nutritional status (p<0.05).Conclusion The prevalence of hypercholesterolemia was 28.4 %.There was an association between hypercholesterolemia and nutri-tional status, with a tendency of hypercholesterolemia to occur atoverweight nutritional status, especially in the urban area